Nanovirus Disease Complexes: An Emerging Threat in the Modern Era - Lal, Aamir; Vo, Thuy Thi Bich; Sanjaya, I Gusti Ngurah Prabu Wira; Ho, Phuong Thi; Kim, Ji-Kwang; Kil, Eui-Joon; Lee, Sukchan (Frontiers in Plant Science, 2020)
Multipartite viruses package their genomic segments independently and mainly infect plants; few target animals. Nanoviridae is a family of multipartite single-stranded DNA plant viruses that individually encapsidate single-stranded DNAs of approximately 1 kb and transmit them through aphids without replication in the aphid vectors, thereby causing important diseases of leguminous crops and banana. Significant findings regarding nanoviruses have recently been made on important features, such as their multicellular way of life, the transmission of distinct encapsidated genome segments through the vector body, evolutionary ambiguities, mode of infection, host range and geographical distribution. This review deals with all the above-mentioned features in view of recent advances with special emphasis on the emergence of new species and recognition of new host range of nanoviruses and aims to shed light on the evolutionary linkages, the potentially devastating impact on the world economy, and the future challenges imposed by nanoviruses.